Selective extraction based on poly(MAA‐VB‐EGMDA) monolith followed by HPLC for determination of hordenine in plasma and urine samples. (30th October 2014) - Chen, Yonggang; Meng, Junhua; Zou, Jili; An, Jing
Abstract Hordenine is an active compound found in several foods, herbs and beer. In this work, a novel sorbent was fabricated for selective solid‐phase extraction (SPE) of hordenine in biological samples. The organic polymer sorbent was synthesized in one step in the plastic barrel of a syringe by a pre‐polymerization solution consisting of methacrylic acid (MAA), 4‐vinylphenylboronic acid (VB) and ethylene glycol dimethacrylate (EGDMA). The conditions for preparation were optimized to generate a poly(MAA‐VB‐EGMDA) monolith with good permeability. The monolith exhibited good enrichment efficiency towards hordenine. By using tyramine as the internal standard, a poly(MAA‐VB‐EGMDA)‐based SPE‐HPLC method was established for analysis of hordenine. Conditions for SPE, including volume of eluting solvent, pH of sample solution, sampling rate and sample volume, were optimized. The proposed SPE‐HPLC method presented good linearity (R2 = 0.9992) within 10–2000 ng/mL and the detection limits was 3 ng/mL, which is significantly more sensitive than reported methods. The method was also applied in plasma and urine samples; good capability of removing matrices was observed, while hordenine in low content was well extracted and enriched. The recoveries were from 90.6 to 94.7% and from 89.3 to 91.5% for the spiked plasma and urine samples, respectively, with the relative standard deviations <4.7%. Copyright © 2014 John Wiley & Sons, Ltd.